Factors Affecting the Provision of Supplementary Food to Infants Under the Age of Six Months in the Working Area of Peukan Bada Health Center, Aceh Besar District - Cut Yuniwati; Nurfajriah Nurfajriah (Institute of Computer Science (IOCS), 2022)
The group is a period where malnutrition is prone to occur, so special attention needs to be given at this age. Malnutrition at this time will have a long-term impact. The impact that can arise on malnutrition is the disruption of growth and development which is a short-term impact and a high risk of developing non-communicable diseases as an adult as a long-term impact. Fear of malnutrition under five, some mothers give additional food to infants under six months; therefore, the purpose of this study is to analyze the factors that influence mothers to give additional food to infants aged less than six months in the working area of Pekan Bada Public Health Center, Aceh Besar District. . This research is a descriptive-analytic study with a cross-sectional study approach. The population in this study were all mothers who had babies aged 0-6 months who were recorded from January to June in the working area of Pekan Bada Health Center, Aceh Besar District, as many as 102 mothers. The sample in this study were mothers who had babies aged 0-6 months who visited Peukan Bada Health Center from January to June 2021. Sampling was done using the Simple Random Sampling technique. The study results found an influence of family support on providing additional food for infants less than six months old in the Work Area of the Pekan Bada Health Center, Aceh Besar District, in 2019. With the results of the chi-square test, it was obtained p-value = 0.005 or p-value < = 0.05. There is an influence between maternal health conditions on the provision of additional food to infants less than 6 months old ( p-value = 0.009) or p-value < = 0.05. Infant Health Conditions influence infant health conditions on giving additional food to infants under six months old, as evidenced by the chi-square test results obtained p-value = 0.020s or p-value < = 0.05.